The Study of Derrida’s Deconstruction in the Short Story “Kembang Dewaretna” by Yanusa Nugroho - Rauf, Ramis; Ulya, Afriani (AL LUGHAWIYAAT: JOURNAL OF ENGLISH LANGUAGE TEACHING, 2025)
This paper reveals the main problem regarding the author's efforts in presenting the reversal of the hierarchy of the character Danaraja who experiences defeat in the short story "Kembang Dewaretna". To answer this problem, this study uses Jacques Derrida's deconstruction theory. Deconstruction is a theory in literary research that rejects the view that language has a definite, certain, and constant meaning as in the classical structuralist view. This rejection occurs because of the separation of space between the signifier and the signified which is considered absolute in the form of traces behind the traces. The method used in this study is deconstruction. This method explains that deconstructing a discourse or literary text shows the collapse of the underlying philosophy or is in hierarchical opposition (binary opposition) to something that is its basis through the identification of operational forms of rhetoric in the text. The results of the study reveal that deconstruction in the short story "Kembang Dewaratna" is a reversal of the hierarchy between the characters Rahwana and Danaraja. The character Rahwana is always narrated as the winner in every battle, while Danaraja is a character who always experiences defeat. In the short story "Kembang Dewaretna", the reversal of the hierarchy is shown by showing the victory of the figure of Danaraja in the fight against Rahwana. Thus, it is concluded that the form of Danaraja's victory is a deconstruction of the elimination of the figure of Rahwana as the center who always appears with his victory.